2004
DOI: 10.1094/phyto.2004.94.7.789
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Sibling Fungal Plant Pathogens in Relation to Host Specialization

Abstract: Sibling plant pathogens can be grouped according to their host rangesthe following groups: group 1, sibling pathogens with nonoverlapping host ranges; group 2, sibling pathogens with both overlapping and nonoverlapping host ranges; and group 3, sibling pathogens with overlapping host ranges. Using the adaptive dynamics methodology, we investigated the evolution of sibling pathogens in relation to host specialization for groups 1 to 3. In particular, we focused on the role of multiple host niches and a trade-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 41 publications
(33 reference statements)
0
31
0
1
Order By: Relevance
“…This is somewhat simplistic because experimental studies demonstrate that the offspring of a plant pathogen can sometimes be phenotypically very different from its parent (global mutations). However, the results of computer simulations (Gudelj et al 2004) show that the evolutionary outcomes do not qualitatively change when both global and local mutations are taken into account. Global mutations are expected to influence the outcome only in the sigmoidal (steep convex-concave) case where the following is anticipated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is somewhat simplistic because experimental studies demonstrate that the offspring of a plant pathogen can sometimes be phenotypically very different from its parent (global mutations). However, the results of computer simulations (Gudelj et al 2004) show that the evolutionary outcomes do not qualitatively change when both global and local mutations are taken into account. Global mutations are expected to influence the outcome only in the sigmoidal (steep convex-concave) case where the following is anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of such pathogen groups can be found within the Botrytis genus (Holliday 1989) where B. cinerea is a generalist whereas B. fabae is a specialist. It is important to note, however, that without the analytical advantages of the adaptive dynamics which clearly identify the importance of the trade-off shape, the computational study in Gudelj et al (2004) lacks generality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease is caused by a complex of Leptosphaeria species (Mendes-Pereira et al, 2003), the most important of which is L. maculans, associated with damaging stem base canker in many countries . In Europe and North America, L. maculans often co-exists with L. biglobosa (West et al, 2002a), which may have evolved from a common ancestor (Gudelj et al, 2004). Leptosphaeria biglobosa is associated with upper stem lesions; whilst generally not damaging, they can cause serious losses in countries like Poland with high summer temperatures (Huang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…(For an introduction to concepts, ideas, and methods developed by the authors of Metz et al [1992Metz et al [ , 1996, Dieckmann and Law [1996], Geritz et al [1998], and others, see Diekmann [2004].) 5 E-mail: fhamelin@agrocampus-ouest.fr plant parasites, Gudelj et al (2004a, b) showed that evolutionary branching can occur, provided there is a (convex) trade-off between parasite transmission capacities on distinct host types. Regarding Manuscript received 23 December 2010; revised 6 May 2011; accepted 1 July 2011.…”
Section: Introductionmentioning
confidence: 99%